Problems and Solution of Malabsorption Syndrome in Indonesia - Suharjono Suharjono; Sunoto Sunoto; Aswitha Budiarso; Titut S. Pusponegoro; W.A.F.J. Tumbelaka (Indonesian Pediatric Society, 1978)
I. Problems of malabsorption syndrome in developing countries like lndonesia are associated especially with :(1) Protein Calorie Malnutrition(2) Low Birth Weight(3) Gastroenteritis(4) Post bowel surgery(5) Being unused to drink milk after weaning.They show a big difference with those in developed countries where they usually are correlated with a.o. coeliac disease, cystic fibrosis, etc.II. Solving the problems :a. Since in diarrhoeal patients, with or without PCM, sugar intolerance and or fat malabsorption usually occur, a formula consisting of low or freelactose with easily absorbable fats i.e. MCT or UFA, might be the best solution as a refeeding regimen.b. Besides treating the malabsorption syndrome, other measures are much more important i.e correction of fluid and electrolyte imbalance and treatment of predisposing condition.